Key technologies of AI in customer service system - Zheng WANG; Hua REN; Xuhai LU (Dianxin kexue)
In the customer service system structure,manual seats,work order processing and other links require a lot of manual operations and participation,the cost is high,the efficiency is relatively low,and there will still be a certain percentage of problems and failures that can’t be found and resolved.In the customer service system,the introduction of artificial intelligence technology can solve these problems to a certain extent,reduce costs and improve the overall efficiency and effectiveness of customer service.The key technologies which could be applied to the customer service system in AI were analyzed,including speech recognition,speech synthesis,and natural language processing.The application of new technology in the customer service system of the operator was discussed.The effect in practical application was illustrated by an example.